Use of Fish Oil–Based Lipid Emulsions in Infants With Intestinal Failure–Associated Liver Disease: A Case Series. (February 2014) - St-Jules, David E.; Watters, Corilee A.; Iwamoto, Lynn M.
The use of fish oil–based lipid emulsions (FOLE) in the treatment of intestinal failure–associated liver disease (IFALD) remains investigational. Additional evidence for safety and efficacy, particularly in the neonatal and pediatric populations, is needed. Retrospective chart review was conducted on 10 infants with short bowel syndrome who received FOLE for IFALD. Direct bilirubin concentrations normalized in surviving subjects within 4.1 to 22.7 weeks of starting treatment. Although earlier initiation of FOLE was not associated with more rapid normalization of direct bilirubin concentrations, it trended toward a significant correlation with reduced length of hospital stay ( P = .058). The reduction in direct bilirubin levels and transition from parenteral to enteral feeding were statistically significant within 6 weeks of initiating the FOLE. Subjects did not have impaired growth and did not develop an essential fatty acid deficiency. These infants were discharged from the hospital 7.9 to 42.3 weeks after starting FOLE treatment, and 2 infants had transitioned completely off parenteral nutrition at discharge. In this study, FOLE appeared to be a safe and effective treatment for IFALD in infants with short bowel syndrome. Future studies are necessary to determine whether FOLE can help to prevent or shorten the duration of cholestasis.